Against Cultural Amnesia Through Optimizing The Role of The Youth Generation in Paloh Naga Agrotourism - Rosalina, Teti; Junaidi, Junaidi; Fatmarini, Amalia; Giry, Taufiq Wijaya; Nasution, Najmi Wardina; Febryani, Ayu (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
This article aims to describe strengthening character and love of culture as an effort to fight cultural amnesia through various forms of creativity of the younger generation in Paloh Naga Agrotourism. The research method is an ethnographic method with a naturalistic approach. Collecting data through participatory observation, in-depth interviews, focus group discussions and archiving folklore. The data analysis technique used Spradley ethnographic analysis with a series of analyzes processed using ATLAS.ti software. The research results are; Optimizing the role of the younger generation in cultivating positive characters around Paloh Naga Agrotourism through participation in art training in music, dance, and traditional theatre. While in the field of education, through participation in the Lingkaran Community Learning Activity Center, the program consists of Character Education, Cashier Education (Coastal Children's Area), Taqsir (Taqlimul Qur'an for Coastal Children), Community Reading Parks, and teaching at the Rehabilitation Workshop of the National Narcotics Agency, Deli Serdang District. Furthermore, efforts to fight cultural amnesia in the aspect of cultural love by participating in various activities related to folklore, namely oral folklore performances in the performance of the Paloh Naga Legend ballet, partially oral folklore performances in traditional dance and game practices, and non-verbal folklore training in the course of product exhibitions and traditional cuisine. Furthermore, the regeneration process of the younger generation in fighting cultural amnesia begins with participating in character and art education after fulfilling the requirements to become a volunteer-based on qualifications. Finally, the forms of creativity displayed by the younger generation, include preparing various folklore performances, creating creative dances, playing traditional music and traditional games to strengthen social interaction and the value of creativity, and creating various traditional cuisines.